Experiential Meaning In T.S. Eliot’s The Waste Land - Affum, G.M. (University Of Ghana, 2021)
This study examines The Waste Land, a seminal poem by Thomas Stearne Eliot, from the Systemic Functional Grammar perspective. Using transitivity as a tool from the Experiential metafunction of the Systemic Functional Grammar, this work explores how Eliot’s grammatical choices construe his experience of the world around and within him in order to unpack the meanings encoded in the poem. To do this, the study used all the three grammatical components that the framework proposes: the processes, participants and circumstances. The work combined both the qualitative and quantitative research methodology. The analysis was done by using Burton’s (1982) steps in text analysis: parsing the clauses in the poem and determining what types of processes exist, what participants are engaged in which type of process and verifying who or what is being affected by each process, and the message that the circumstantial elements presents about the background of the poem. The analysis of the work revealed that all the three major process types: material, relational and mental processes were present in the overall transitivity analysis. Eliot uses these processes and its attendant participants and circumstances to reveal a world characterized by chaos, degeneration, desolation, sexual sterility, decay, transience, horror, lifelessness and a faint hope for regeneration. The study adds a new dimension to the study of Eliot’s poems.
MPhil. English
Keywords: The Waste Land; Eliot; poem; sexual sterility; lifelessness